Real-Time Analytics Dashboards for Emergency Business Continuity and Crisis Decision Support - Benjamin Monday Ojonugwa,; Bisi Ogunwale,; Oluwasanmi Segun Adanigbo,; Akoche Ochefu, (International Journal of Scientific Research in Science and Technology, 2025)
This paper proposes a framework for designing and implementing real-time analytics dashboards to support emergency business continuity and crisis decision-making. Leveraging technologies such as big data analytics, artificial intelligence (AI), and cloud computing, the framework enables organizations to monitor critical metrics, predict disruptions, and make informed decisions during crises. A systematic literature review synthesizes insights on dashboard design, data integration, and crisis management, while case studies across logistics, healthcare, and finance validate the framework’s applicability. Findings demonstrate that real-time dashboards can reduce response times by up to 50%, improve decision accuracy by 40%, and enhance operational resilience. The study contributes to the literature on crisis management and offers practical guidelines for organizations aiming to strengthen business continuity.
Keywords: Big Data Analytics; Business Continuity; Cloud Computing; Crisis Decision Support; Data Integration